2020
DOI: 10.1051/0004-6361/202038289
|View full text |Cite
|
Sign up to set email alerts
|

Gas and dust from metal-rich AGB stars

Abstract: Context. Stars evolving through the asymptotic giant branch (AGB) phase provide significant feedback to their host system, which is both gas enriched in nuclear-burning products, and dust formed in their winds, which they eject into the interstellar medium. Therefore, AGB stars are an essential ingredient for the chemical evolution of the Milky Way and other galaxies. Aims. We study AGB models with super-solar metallicities to complete our vast database, so far extending from metal-poor to solar-chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 95 publications
(180 reference statements)
1
53
1
Order By: Relevance
“…The nucleosynthesis prescriptions are the same as model MWG-11 of Romano et al (2019). For low-and intermediate-mass stars with initial masses in the range 1 ≤ m/M < 9, we adopted the yields by Ventura et al (2013Ventura et al ( , 2020 that include a proper treatment of the super-AGB phase for the most massive AGB stars. For massive stars with 13 ≤ m/M ≤ 100, we adopted the yields by Limongi & Chieffi (2018).…”
Section: Nucleosynthesis Prescriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleosynthesis prescriptions are the same as model MWG-11 of Romano et al (2019). For low-and intermediate-mass stars with initial masses in the range 1 ≤ m/M < 9, we adopted the yields by Ventura et al (2013Ventura et al ( , 2020 that include a proper treatment of the super-AGB phase for the most massive AGB stars. For massive stars with 13 ≤ m/M ≤ 100, we adopted the yields by Limongi & Chieffi (2018).…”
Section: Nucleosynthesis Prescriptionsmentioning
confidence: 99%
“…Because of the assumed fast evolution (see Grisoni et al 2017), coupled to negligible production of 7 Li from both massive AGB stars (Ventura et al 2000(Ventura et al , 2020 and GCRs (Romano et al 2001;Prantzos 2012) at the relevant metallicities, the abundance of 7 Li is predicted to remain almost flat during most of the thick-disc evolution (see also Guiglion et al 2016;Grisoni et al 2019). 10 Possible production or destruction of 7 Li due to extra mixing processes, such as thermohaline mixing in low-mass, bright RGB stars and stellar rotation (Charbonnel et al 2020), are not included in the adopted stellar models and yields (Ventura et al 2013(Ventura et al , 2020 2009) is indicated with the multiplication sign. The predictions of the parallel GCE model are highlighted with different colours depending on the assumptions made about 7 Li synthesis and cosmological lithium abundance.…”
Section: Evolution Of Lithium In the Solar Vicinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mid-infrared observations show the presence of alumina dust (amorphous Al 2 O 3 ) in the extended envelopes of O-rich AGB stars. Although only recent condensation experiments confirmed that amorphous alumina can condense in circumstellar conditions [5], intermediate mass (IM) AGB stars have been considered to be the main source of alumina dust in the galaxy for many years, starting from the first work by Onaka et al [6], to the most recent ones Dell'Agli et al [7], Ventura et al [8] (and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, group 4 silicates are overabundant compared to those of groups 1 and 2 (likely because of the injection of materials from a nearby supernova into the solar nebula [20]); while group 2 silicates are rarer than oxides. Such a lack could be accounted for by the fact that silicates are expected to form mainly in IM AGBs affected by HBB [7,8]. Left panel: oxygen isotopic ratios in presolar oxide grains.…”
Section: Introductionmentioning
confidence: 99%